Self-cleaning glass and preparation method thereof
By coating a self-cleaning slurry of specific composition on the glass surface, the problem of contaminants accumulation on the glass surface is solved, and the self-cleaning effect and corrosion resistance are improved, reducing maintenance costs.
Patent Information
- Application Number
- CN202411467353.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-18
AI Technical Summary
The glass surface is prone to accumulation of pollutants and requires regular manual cleaning, which increases costs and has adverse effects on the environment.
The self-cleaning slurry is applied on the glass substrate, and after curing, it forms a self-cleaning glass with excellent self-cleaning effect and corrosion resistance. The slurry consists of methylalkoxysilane, modified talc, isopropanol, secondary amino modified silicone oil, dodecyl esters, chitosan, vapor phase silica, polyvinylpyrrolidone and water.
Effectively prevent dust and water from adhering, remove surface contaminants, significantly improve self-cleaning effect and corrosion resistance, and reduce maintenance costs.
Smart Images

Figure SMS_7
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to self-cleaning glass and a preparation method thereof. Background Art
[0002] With the rapid development of the construction and automobile industries, the frequency and scope of glass, as the main material for building curtain walls and vehicle windshields, are constantly expanding. However, glass is easily attached to external pollutants (such as dust, dirt, oil stains, rain, etc.), resulting in a decrease in its light transmittance and aesthetics. Especially in high-rise buildings and vehicles, cleaning glass requires a lot of manpower, time and resources. Therefore, how to develop glass with self-cleaning function, reduce maintenance costs and improve application value has become an important topic in glass material research.
[0003] Traditional glass surfaces are prone to accumulation of pollutants and require regular manual cleaning or maintenance with the help of cleaning equipment, which not only increases costs but may also have an adverse impact on the environment.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The invention provides a self-cleaning glass and a preparation method thereof. The self-cleaning glass has excellent self-cleaning effect and anti-corrosion performance.
[0006] The present invention solves the technical problem by adopting the following technical solutions: A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry is coated on a glass substrate and cured to obtain a self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 42-50 parts of methyl alkoxy silane, 15-24 parts of modified talc, 6-10 parts of isopropanol, 4-8 parts of secondary amine-modified silicone oil, 2-5 parts of dodecyl ester, 0.5-2 parts of chitosan, 0.2-0.8 parts of fumed silica, 0.2-0.8 parts of polyvinyl pyrrolidone, and 15-20 parts of water.
[0007] The self-cleaning slurry of the present invention can effectively protect glass and prevent dust and water from adhering. The coating has good adhesion to the glass substrate, effectively removes surface pollutants, and effectively improves the self-cleaning effect and anti-corrosion performance.
[0008] As a preferred embodiment of the present invention, the viscosity of the secondary amine-modified silicone oil at 25° C. is 650-800 mPa·s.
[0009] As a preferred embodiment of the present invention, the preparation method of the modified talc is: (1) adding talcum powder and nitric acid solution into sulfuric acid solution, stirring evenly, then adding ammonia solution, stirring evenly, and drying to obtain pretreated talcum powder; (2) adding a fluorinated silane coupling agent and azobisisobutyronitrile to γ-acryloxypropyltrimethoxysilane, reacting at 65-75° C. for 2-4 hours to obtain a modifier; (3) Add pretreated talcum powder, modifier and anhydrous ethanol into water and stir evenly at 45-60°C to obtain a precursor solution; (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly, perform ultrasonic treatment, filter, and dry to obtain modified talc.
[0010] The invention firstly performs acid treatment and ammonia modification treatment on talc powder to effectively improve the activity and the content of surface functional groups, and then uses fluorine-containing silane coupling agent and gamma-acryloxypropyltrimethoxysilane for synthesis to obtain a modifier with excellent hydrophobic effect, which can effectively improve the hydrophobic effect, and then performs paraffin wax and sodium ditridecyl sulfosuccinate coating treatment to effectively improve the dispersion effect and compatibility of talc powder in the system, and a low surface energy layer is formed on the surface of the modified talc powder, so that water droplets and dust are difficult to adhere to the surface, and when water droplets fall on the surface of the material, they are in a ball shape, taking away the dirt and dust on the surface, and achieving a self-cleaning effect.
[0011] As a preferred embodiment of the present invention, the mass ratio of the talc powder, nitric acid solution, sulfuric acid solution and ammonia solution is 1: (0.1-0.3): (2-5): (0.1-0.2).
[0012] As a preferred embodiment of the present invention, the molar concentration of the nitric acid solution is 0.5~2 mol / L; the molar concentration of the sulfuric acid solution is 0.5~2 mol / L; the molar concentration of the ammonia solution is 0.5~2 mol / L.
[0013] As a preferred embodiment of the present invention, the mass ratio of the fluorine-containing silane coupling agent, azobisisobutyronitrile, and γ-acryloxypropyltrimethoxysilane is 1: (0.02-0.05): (0.8-1.2); The fluorine-containing silane coupling agent includes at least one of tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
[0014] As a preferred embodiment of the present invention, the mass ratio of the pretreated talcum powder, the modifier, the anhydrous ethanol and the water is 1: (0.1-0.2): (0.5-0.8): (2-4).
[0015] As a preferred embodiment of the present invention, the mass ratio of the paraffin wax, sodium ditridecyl sulfosuccinate, and the precursor solution is (0.04-0.08): (0.02-0.06): 1.
[0016] As a preferred embodiment of the present invention, the curing temperature is 110-140° C., and the curing time is 90-150 min.
[0017] The present invention also provides a self-cleaning glass, which is prepared by the above-mentioned preparation method.
[0018] Beneficial effects of the present invention: The self-cleaning slurry described in the present invention can effectively protect glass and prevent dust and water from adhering. The coating has good adhesion to the glass substrate, effectively removes surface pollutants, and effectively improves the self-cleaning effect and anti-corrosion performance. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0021] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0022] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0023] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained commercially. The raw materials used in the comparative examples and the raw materials used in the parallel experiments of the embodiments are the same commercially available products unless otherwise specified.
[0024] Example 1 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 45 parts of methyl alkoxysilane, 20 parts of modified talc, 8 parts of isopropanol, 5 parts of secondary amine-modified silicone oil, 3 parts of dodecyl ester, 1 part of chitosan, 0.5 parts of fumed silica, 0.5 parts of polyvinyl pyrrolidone, and 17 parts of water.
[0025] The viscosity of the secondary amine-modified silicone oil (brand name Shin-Etsu silicone KF-880) at 25° C. is 650 mPa·s.
[0026] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0027] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0028] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0029] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0030] Example 2 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 50 parts of methyl alkoxy silane, 15 parts of modified talc, 10 parts of isopropanol, 8 parts of secondary amine-modified silicone oil, 5 parts of dodecyl ester, 2 parts of chitosan, 0.8 parts of fumed silica, 0.8 parts of polyvinyl pyrrolidone, and 20 parts of water.
[0031] The viscosity of the secondary amine-modified silicone oil (brand name Shin-Etsu silicone KF-880) at 25° C. is 650 mPa·s.
[0032] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0033] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0034] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0035] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0036] Example 3 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 42 parts of methyl alkoxy silane, 24 parts of modified talc, 6 parts of isopropanol, 4 parts of secondary amine-modified silicone oil, 2 parts of dodecyl ester, 0.5 parts of chitosan, 0.2 parts of fumed silica, 0.2 parts of polyvinyl pyrrolidone, and 15 parts of water.
[0037] The viscosity of the secondary amine-modified silicone oil (brand name Shin-Etsu silicone KF-880) at 25° C. is 650 mPa·s.
[0038] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0039] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0040] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0041] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0042] Example 4 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 45 parts of methyl alkoxysilane, 20 parts of modified talc, 8 parts of isopropanol, 5 parts of secondary amine-modified silicone oil, 3 parts of dodecyl ester, 1 part of chitosan, 0.5 parts of fumed silica, 0.5 parts of polyvinyl pyrrolidone, and 17 parts of water.
[0043] The viscosity of the secondary amine-modified silicone oil (brand name Shin-Etsu silicone KF-8004) at 25° C. is 800 mPa·s.
[0044] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0045] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0046] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0047] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0048] Example 5 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 45 parts of methyl alkoxysilane, 20 parts of modified talc, 8 parts of isopropanol, 5 parts of secondary amine-modified silicone oil, 3 parts of dodecyl ester, 1 part of chitosan, 0.5 parts of fumed silica, 0.5 parts of polyvinyl pyrrolidone, and 17 parts of water.
[0049] The viscosity of the secondary amine-modified silicone oil (brand name: Shin-Etsu silicone KF-860) at 25° C. is 250 mPa·s.
[0050] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0051] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0052] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0053] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0054] Example 6 A method for preparing self-cleaning glass comprises the following steps: The self-cleaning slurry was applied to a 10 mm thick glass substrate (1 mm 1m), the coating thickness is 1200nm, and it is cured at 140℃ for 120min to obtain self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 45 parts of methyl alkoxysilane, 20 parts of modified talc, 8 parts of isopropanol, 5 parts of secondary amine-modified silicone oil, 3 parts of dodecyl ester, 1 part of chitosan, 0.5 parts of fumed silica, 0.5 parts of polyvinyl pyrrolidone, and 17 parts of water.
[0055] The viscosity of the secondary amine-modified silicone oil (brand name Shin-Etsu silicone KF-864) at 25° C. is 3500 mPa·s.
[0056] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0057] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Add pretreated talcum powder, modifier, and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol, and water is 1:0.15:0.6:3.
[0058] (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, perform ultrasonic treatment at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and the precursor solution is 0.06:0.05:1.
[0059] The preparation method of the self-cleaning slurry is as follows: methyl alkoxy silane, isopropanol and water are mixed uniformly at a rotation speed of 500 rpm, and then modified talcum powder, secondary amine modified silicone oil, dodecyl ester, 1 part of chitosan, fumed silica and polyvinyl pyrrolidone are added, and the mixture is stirred uniformly at a rotation speed of 500 rpm to obtain the self-cleaning slurry.
[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the composition of the self-cleaning slurry is different. In this comparative example, an equal amount of talcum powder is used to replace the modified talcum powder, and the other contents are the same.
[0061] The self-cleaning slurry comprises the following raw materials in parts by weight: 45 parts of methyl alkoxysilane, 20 parts of 1250-mesh talc, 8 parts of isopropanol, 5 parts of secondary amine-modified silicone oil, 3 parts of dodecyl ester, 1 part of chitosan, 0.5 parts of fumed silica, 0.5 parts of polyvinyl pyrrolidone, and 17 parts of water.
[0062] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the preparation method of the modified talc is different, and the other aspects are the same.
[0063] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0064] (2) Add pretreated talcum powder, γ-acryloxypropyltrimethoxysilane and anhydrous ethanol into water, and stir evenly at 500 rpm at 55° C. to obtain a precursor solution; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol and water is 1:0.15:0.6:3.
[0065] (3) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly at 500 rpm, ultrasonically treat at 500 W for 30 min, filter, and dry to obtain modified talc. The mass ratio of the paraffin wax, sodium tridecyl sulfosuccinate, and precursor solution is 0.06:0.05:1.
[0066] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the preparation method of the modified talc is different, and the other aspects are the same.
[0067] The preparation method of the modified talcum powder is: (1) Add 1250 mesh talc and 1 mol / L nitric acid solution to 1 mol / L sulfuric acid solution, stir evenly, then add 1 mol / L ammonia solution, stir evenly at a speed of 500 rpm, and dry to obtain pretreated talc; the mass ratio of the talc, nitric acid solution, sulfuric acid solution, and ammonia solution is 1:0.2:4:0.15.
[0068] (2) adding tridecafluorooctyl trimethoxysilane and azobisisobutyronitrile to γ-acryloxypropyl trimethoxysilane, and reacting at 70° C. for 3 hours to obtain a modifier; the mass ratio of tridecafluorooctyl trimethoxysilane, azobisisobutyronitrile, and γ-acryloxypropyl trimethoxysilane is 1:0.04:1; (3) Adding pretreated talcum powder, modifier and anhydrous ethanol into water, stirring evenly at 500 rpm at 55° C. to obtain a precursor solution, filtering and drying to obtain modified talcum powder; the mass ratio of the pretreated talcum powder, modifier, anhydrous ethanol and water is 1:0.15:0.6:3.
[0069] Test Case 1. Use a contact angle meter to measure the water contact angle.
[0070] 2. Salt spray resistance: Tested according to GB / T1771-2007, simulating the corrosion resistance of the coating in a marine environment for 4000h.
[0071] Table 1
[0072] It can be seen from Table 1 that the self-cleaning glass of the present invention has excellent self-cleaning effect and excellent anti-corrosion performance.
[0073] Comparison of Examples 1, 4 to 6 shows that the present invention uses a secondary amine group with a viscosity of 650 to 800 mPa·s to further improve the self-cleaning effect and anti-corrosion performance.
[0074] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the modified talc powder described in the present invention can significantly improve the self-cleaning effect and anti-corrosion performance, and the modified talc powder prepared by different methods has different improvements in self-cleaning effect and anti-corrosion performance. The modified talc powder prepared by the method of the present invention can more significantly improve the self-cleaning effect and anti-corrosion performance than the modified talc powder prepared by other methods.
[0075] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing self-cleaning glass, characterized in that: The following steps are involved: The self-cleaning slurry is coated on a glass substrate and cured to obtain a self-cleaning glass; The self-cleaning slurry comprises the following raw materials in parts by weight: 42-50 parts of methyl alkoxy silane, 15-24 parts of modified talc, 6-10 parts of isopropanol, 4-8 parts of secondary amine-modified silicone oil, 2-5 parts of dodecyl ester, 0.5-2 parts of chitosan, 0.2-0.8 parts of fumed silica, 0.2-0.8 parts of polyvinyl pyrrolidone, and 15-20 parts of water.
2. The method for preparing self-cleaning glass according to claim 1, characterized in that: The viscosity of the secondary amine-modified silicone oil at 25° C. is 650-800 mPa·s.
3. The method for preparing self-cleaning glass according to claim 1, characterized in that: The preparation method of the modified talcum powder is: (1) adding talcum powder and nitric acid solution into sulfuric acid solution, stirring evenly, then adding ammonia solution, stirring evenly, and drying to obtain pretreated talcum powder; (2) adding a fluorinated silane coupling agent and azobisisobutyronitrile to γ-acryloxypropyltrimethoxysilane, reacting at 65-75° C. for 2-4 hours to obtain a modifier; (3) Add pretreated talcum powder, modifier and anhydrous ethanol into water and stir evenly at 45-60°C to obtain a precursor solution; (4) Add paraffin wax and sodium tridecyl sulfosuccinate to the precursor solution, stir evenly, perform ultrasonic treatment, filter, and dry to obtain modified talc.
4. The method for preparing self-cleaning glass according to claim 3, characterized in that: The mass ratio of the talcum powder, nitric acid solution, sulfuric acid solution and ammonia solution is 1: (0.1-0.3): (2-5): (0.1-0.2).
5. The method for preparing self-cleaning glass according to claim 3, characterized in that: The molar concentration of the nitric acid solution is 0.5-2 mol / L; the molar concentration of the sulfuric acid solution is 0.5-2 mol / L; and the molar concentration of the ammonia solution is 0.5-2 mol / L.
6. The method for preparing self-cleaning glass according to claim 3, characterized in that: The mass ratio of the fluorine-containing silane coupling agent, azobisisobutyronitrile and γ-acryloxypropyltrimethoxysilane is 1: (0.02-0.05): (0.8-1.2); The fluorine-containing silane coupling agent includes at least one of tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
7. The method for preparing self-cleaning glass according to claim 3, characterized in that: The mass ratio of the pretreated talcum powder, the modifier, the anhydrous ethanol and the water is 1: (0.1-0.2): (0.5-0.8): (2-4).
8. The method for preparing self-cleaning glass according to claim 3, characterized in that: The mass ratio of the paraffin wax, sodium ditridecyl sulfosuccinate and the precursor solution is (0.04-0.08): (0.02-0.06):
1.
9. The method for preparing self-cleaning glass according to claim 1, characterized in that: The curing temperature is 110-140° C., and the curing time is 90-150 minutes.
10. A self-cleaning glass, characterized in that: The method is prepared by any one of claims 1 to 9.